Explorations of Beliefs about EFL Teachers’ Roles from Both Teachers’ and Students’ Perspectives through Metaphor Analysis - Azeez, Sharihan Shawkat (European Scientific Journal, ESJ, 2020)
Metaphor acts as a window into comprehending teachers’ experiences through providing insights into complex concepts of teaching and learning. As a result, it plays a crucial role in exploring beliefs about teachers’ roles in the teaching and learning process. To elicit ideas and beliefs which both teachers and students held about the role of English teachers, questionnaires were given to 30 teachers and 85 students in the University of Duhok, English Department. The questionnaire asked the subjects to provide their beliefs about English teachers’ roles by using a sentence completion task “An English teacher is…. because….”. Eight conceptual categories are introduced from the linguistic metaphors and example metaphors for each category are given in the results tables. The eight conceptual categories include: teacher as devotee, teacher as nurturer, teachers as provider / source of knowledge, teacher as cultural transmitter, teacher as authority, teacher as guider, teacher as a friend, and teacher as a nice beautiful soul. All participants expressed the same conceptual categories, but still they use different metaphors to express their views. An interesting feature of these results is that there are some parallel and overlaps of metaphors among different subjects. The findings of this study suggested subtle differences between students’ and teachers’ beliefs. This study will benefit teachers, curriculum designers, and researchers. Researchers may carry out comprehensive studies using metaphor as an investigating tool to better understand both students and teachers’ perceptions of the teachers’ roles. The results will help develop comprehensive and inclusive methods of teaching. Larger samples with variables such as gender, age, different locations, and proficiency of participants should be taken into consideration during future studies.